Textural and compositional evidence for a polyphase saturation of tourmaline in granitic rocks from the Trebic Pluton (Bohemian Massif) - Burianek,D.; Dolnicek,Z.; Novak,M. (Journal of Geosciences, 2016)
Crystallization of granite melts produced several textural types of granites and pegmatites in the Trebic Pluton: dykes of volumetrically dominant muscovite-biotite granite (MBG) locally containing tourmaline nodules with leucocratic halos, minor oval pods to dykes of tourmaline granite and veins of tourmaline pegmatite, both enclosed in MBG. An aplitic zone with comb textures, locally developed in MBG along the contact with surrounding durbachites, suggests high degree of undercooling. Evidence for polyphase saturation of tourmaline was observed within MBG and related granitic rocks including the following textural and compositional types of tourmaline: (i) tourmaline nodules surrounded by a leucocratic halos; (ii) euhedral to subhedral grains of tourmaline randomly distributed within tourmaline granite and tourmaline-quartz accumulations with leucocratic halos in the marginal part of granite dykes; (iii) rare columnar crystals of black tourmaline occurring locally in central parts of pegmatite; (iv) dravite-rich rims and late dravite veinlets in tourmaline grains from nodules, suggesting crystallization from hydrothermal fluids in the system open to host rocks as supported also by fluid inclusions study. The dominant substitutions in tourmaline include Fe Mg-1, XNaYR2+WF X▯YAl-1WOH-1 and YR2+WO YAl-1WOH-1. Based on zircon and monazite thermometry, near-solidus temperatures of c. 700-660 °C and 680-640 °C were estimated for the central part of the MBG dykes and the volatile-rich tourmaline granite, respectively.
Keywords: tourmaline; chemical composition; granite; pegmatite; magma evolution; fluid inclusions